Toward a relationship paradigm: an auto-narrative reflexive ethnography of co-participation and co-construction of the culture of meaning - Tracy, John R., author; Gloeckner, Gene W., advisor; Banning, James H., committee member; Schatz, Mona C. Struhasker, committee member; Gonzales-Walker, Roxanne M., committee member (Colorado State University. Libraries, 2005)
This study is a reflexive ethnography in which the material unfolds using a combination of the author's relationship epistemology and axioms from systemic human communication theory (Watzlawick, Beavin, and Jackson, 1967) as a basis for culture of meaning analysis (CMA). The purpose is to understand how the data illuminate co-participation and co-construction of the culture of meaning. This is done reflexively assuming "that where there is meaning, there is culture" (Ellis and Bochner, 1996, p. 16). Three sets of data include the author's personal narrative (1945 to 1961), State of Iowa records (1956 to 1961) regarding the author's institutionalization and foster care, and the literature review with focus on the historical and theoretical context related to the epistemology, methodology, the time periods, child welfare, foster care, and geographic location. The introduction begins the unfolding process by clarifying the purpose, concepts, questions, focus, significance, and the researcher's perspective. This is expanded with an unfolding of the literature in relation to the co-participants in the study and its design. Chapter three develops the methodology particular to the nature of and purpose of the study. Chapter four opens the two main data sets by means of a descriptive analysis of the co-participants. Chapters five and six relate a reflexive process of analysis of the relationship messages and relationship perceptions of the co-participants of each other in a way that the reader is allowed to co-participate in the unfolding process of the culture of meaning. These chapters are divided between the author's (Johnny's) institutionalization and foster care experience. It is in these chapters that the richness of the culture of meaning is unfolded for full view of the reader. Chapter seven provides a degree of conclusion to the study, but the nature of the study is not one of conclusion, but rather to unfold for view the culture of meaning. As an ongoing here and now process, it does not end with this dissertation. You the readers continue the dialogue, expand, and redefine anew the culture of meaning.
Keywords: cultural anthropology